1995
DOI: 10.1002/mrm.1910330306
|View full text |Cite
|
Sign up to set email alerts
|

Changes in T2*‐Weighted Images During Hyperoxia Differentiate Tumors from Normal Tissue

Abstract: Experiments were performed to determine whether changes in T2*-weighted MR images during and after hyperoxia differentiate tumors from normal tissue. Mammary adenocarcinomas implanted in the right hind limbs of rats were studied. Gradient echo images were obtained at 2 Tesla with an evolution time of 20 ms and a recycle time of 1 s. Breathing gas was either air or 100% O2. Significant increases in image intensity were observed in tumor centers and rims during hyperoxia while much smaller changes were detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 14 publications
1
20
1
Order By: Relevance
“…The first study using this non-invasive method examined the effect of hyperoxia on T2*-weighted images of rat R3230AC mammary adenocarcinomas (Karczmar et al, 1994). The same group reported that T2*-weighted images differentiated tumours from normal tissue (Kuperman et al, 1995). They reported that significant signal increases were observed within the tumour centre and rim, while little change was observed in muscle during hyperoxia.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The first study using this non-invasive method examined the effect of hyperoxia on T2*-weighted images of rat R3230AC mammary adenocarcinomas (Karczmar et al, 1994). The same group reported that T2*-weighted images differentiated tumours from normal tissue (Kuperman et al, 1995). They reported that significant signal increases were observed within the tumour centre and rim, while little change was observed in muscle during hyperoxia.…”
Section: Discussionmentioning
confidence: 96%
“…Non-invasively, there has been increasing interest in measurements of changes in tissue oxygen tension using magnetic resonance imaging (MRI) methods. Semi-quantitative measurements of the tumour oxygen level have been discussed using oxygenation-sensitive 1 H-MRI measurements during 100% oxygen inhalation (Karczmar et al, 1994;Kuperman et al, 1995;Edelman et al, 1996;Oikawa et al, 1997;Tadamura et al, 1997;Obata et al, 1998). These approaches have been used to increase tumour oxygenation sensitizing to radiotherapy and chemotherapy.…”
mentioning
confidence: 99%
“…This can be explained by a possible extravasation of the contrast agent and/or a passive, hypoxicinduced vasodilation resulting from surrounding vasodilated tissue (Robinson et al, 1999). The large variability in BV values and BV changes in this region may be ascribed to a redistribution of the perfusion within the tumour (Dewhirst et al, 1989;Kuperman et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The high clinical impact of this method in oncologic applications is underlined by numerous animal studies investigating tumor hypoxia (2,3,(16)(17)(18) and vessel maturation and function (19)(20)(21). The feasibility of respiratory challenges in clinical settings has been further demonstrated in several tumor studies in humans (22)(23)(24)(25)(26)(27).The response to hyperoxia and hypercapnia, affecting both oxygenation and blood flow and volume, can be measured using magnetic resonance imaging (MRI), because the related changes in deoxyhemoglobin concentration (dHb) ultimately manifest in changes in the reversible transverse relaxation rate R* 2 (1,28), a relation that is known as the blood-oxygenation-level-dependent (BOLD) effect (29). Furthermore, an increased blood flow also leads to an accelerated inflow of unsaturated spins in slice-selective MR sequences.…”
mentioning
confidence: 99%